2014
DOI: 10.7763/ijiet.2014.v4.450
|View full text |Cite
|
Sign up to set email alerts
|

An Instrument to Measure Math Attitudes of Computer Science Students

Abstract: Although mathematics is one of the essential courses for students in determining college majors, for many students in postsecondary education, mathematics is seen more as a frightening ordeal than a valuable learning experience. Computer science students explicitly use mathematics in many computer science courses. This demands that computer science majors have in-depth math background to become successful in a computer science career. This paper is a report of the initial development of a new instrument to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The self-efficacy category and enjoyment category were taken from the survey by Ali et al (2014) in relation to measuring mathematics attitudes, the participation category from the National Survey of Student Engagement (Noohi et al, 2013), and the understanding category from the Mathematics Beliefs Scale (Lester, 2007). The survey made use of a 4-point Likert scale (1 = Strongly disagree, 2 = Disagree, 3 = Agree, 4 = Strongly agree) to measure the students' level of interest with collaborative learning and their attitudes towards learning mathematics.…”
Section: Surveymentioning
confidence: 99%
“…The self-efficacy category and enjoyment category were taken from the survey by Ali et al (2014) in relation to measuring mathematics attitudes, the participation category from the National Survey of Student Engagement (Noohi et al, 2013), and the understanding category from the Mathematics Beliefs Scale (Lester, 2007). The survey made use of a 4-point Likert scale (1 = Strongly disagree, 2 = Disagree, 3 = Agree, 4 = Strongly agree) to measure the students' level of interest with collaborative learning and their attitudes towards learning mathematics.…”
Section: Surveymentioning
confidence: 99%
“…Knowledge of logical mathematics and its application in programming are essential for complex tasks. Most students have difficulties with mathematical subjects; the correlation between success in programming courses and mathematical courses is still very high (Duran, 2016;Ali et al, 2014;Balmes, 2017).…”
Section: The Role Of Mathematics In Cs Educationmentioning
confidence: 99%
“…It helps the students improve their problem-solving abilities as such studies confirmed that mathematics found to be one of the contributory factors on the success of the students taking information technology program (7,8) . Therefore, students must have a strong background in mathematics to have greater success in taking programming courses (9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that mathematics is found to be significant in relation to computer programming wherein math is an avenue of learning essential skills that is necessary also for learning how to program (7,11) . Several works in literature on the relationship of mathematics and programming have been examined by the researchers to show the relevance of the present study.…”
Section: Introductionmentioning
confidence: 99%